Is gastric cancer preventable?. Issue 9 (11th August 2004) - Correa, P
Abstract : Gastric cancer is a major health burden worldwide and prevention is the most promising strategy to control the disease. The available scientific evidence indicates that curing Helicobacter pylori infection results in a modest retardation of the precancerous process but does not prevent all cancers. Individuals at the highest risk should be cured of their infection and monitored endoscopically to detect dysplasia and "early" cancer, amenable to successful treatment.